2010 Proceedings IEEE INFOCOM 2010
DOI: 10.1109/infcom.2010.5462159
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Sensor Placement for SHM Systems: Refocusing on Application Demands

Abstract: Abstract-There are heavy studies recently on applying wireless sensor networks for structural health monitoring. These works usually focus on the computer science aspect, and the considerations include energy consumption, network connectivity, etc. It is commonly believed that for the current resource limited wireless sensors, system design could be more efficient if the application requirements are incorporated. Nevertheless, we often find that, rather than integration, assumptions have to be made due to lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 25 publications
4
73
0
Order By: Relevance
“…A sensor deployment module using EI is proposed in [22]. This is the first interdisciplinary attempt that integrates the constraints from the civil engineering and the requirements from the computer science that are imposed on WSNs for the sensor placement.…”
Section:  Sensor Placement Using Ei Methods (Spem)mentioning
confidence: 99%
See 2 more Smart Citations
“…A sensor deployment module using EI is proposed in [22]. This is the first interdisciplinary attempt that integrates the constraints from the civil engineering and the requirements from the computer science that are imposed on WSNs for the sensor placement.…”
Section:  Sensor Placement Using Ei Methods (Spem)mentioning
confidence: 99%
“…After finding initial sensor locations through the QR factorization of the mode matrix of a structure, sequential sensor placement method determines an optimal sensor position one at a time. Finally, the genetic algorithm is applied to determine the globally optimal sensor locations SPEM [22] Combined SPEM is an interdisciplinary approach for an OSP problem that integrates both the constraints from the civil engineering and the requirements imposed on a WSN from the computer science domain. energy SPEM [23] Combined SPEM is improved by considering the amount of the energy consumption of a sensor node.…”
Section: Osps [12] Engineering Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies on wireless structural monitoring and control systems were reported in [20,21,27,28]. Realtime transmission scheduling and co-designs for WSANs has been investigated in [11,24,25,31].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, researchers have found that it is also fruitful to apply wireless sensor networks to existing applications to replace or partially replace the wired infrastructure. One example is structural health monitoring (SHM) using wireless sensor networks [3]. The wireless feature has great advantages ranging from a cheaper price, to easy system deployment and modification.…”
Section: Introductionmentioning
confidence: 99%